2021
DOI: 10.47119/ijrp1008611020212317
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Maternal Factors Affecting The Incidence of Low Birth Weight (LBW) at Kanor Health Center, Bojonegoro Regency, East Java

Abstract: Background: Low birth weight (LBW) babies are one of the health problems that are a serious concern in several developing countries. Low birth weight (LBW) is a condition when a baby is born weighing < 2500 grams. LBW contributes 60%-80% of all neonatal deaths in the world. LBW can be caused by factors originating from the mother, fetus or from the surrounding environment. This study aims to analyze maternal factors that influence the incidence of low birth weight (LBW) babies at Kanor Health Center, Bojonegor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Various maternal and child characteristics and contextual and environmental factors found significant in previous literature and/or available in BDHS 2017-18 dataset were used as independent variables in this study [2,4,5,[12][13][14][15][16][17][18][19][20]. Maternal factors included mother's age in years (15-19, 20-24, 25-29, 30-34, 35 and above); parents' educational status (both parents were uneducated, only father was uneducated, only mother was uneducated, both parents were educated); mother currently working (no, yes); underweight mother (no, yes); mothers' decision-making autonomy (not practiced, practiced); mother's attitudes towards violence (not justified, justified); mothers received antenatal care (ANC) (no, yes); the number of living children (≤ 2, ≥ 3); age at first sex in years (< 15, 15-24, 25-34); wanted last child (wanted then, wanted later, wanted no more); ever had terminated pregnancy (no, yes); last birth with a caesarean section (no, yes); and a sign of pregnancy complication (no, yes).…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various maternal and child characteristics and contextual and environmental factors found significant in previous literature and/or available in BDHS 2017-18 dataset were used as independent variables in this study [2,4,5,[12][13][14][15][16][17][18][19][20]. Maternal factors included mother's age in years (15-19, 20-24, 25-29, 30-34, 35 and above); parents' educational status (both parents were uneducated, only father was uneducated, only mother was uneducated, both parents were educated); mother currently working (no, yes); underweight mother (no, yes); mothers' decision-making autonomy (not practiced, practiced); mother's attitudes towards violence (not justified, justified); mothers received antenatal care (ANC) (no, yes); the number of living children (≤ 2, ≥ 3); age at first sex in years (< 15, 15-24, 25-34); wanted last child (wanted then, wanted later, wanted no more); ever had terminated pregnancy (no, yes); last birth with a caesarean section (no, yes); and a sign of pregnancy complication (no, yes).…”
Section: Independent Variablesmentioning
confidence: 99%
“…maternal (age, body mass index, education, occupation, maternal mental stress, maternal weight gain during pregnancy, mother's access to prenatal care, diet during pregnancy and others), environmental (natural disaster, type of toilet facilities, type of drinking water, used solid waste for cooking, etc. ), child (sex of child); and contextual (place of residence, region of residence) factors [2,4,5,[12][13][14][15][16][17][18][19][20][21]. Some previous studies in Bangladesh showed that maternal characteristics; child, and contextual factors were significantly associated with LBW [2,9,12,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%